2019
DOI: 10.1007/s00381-019-04478-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes with respect to extent of surgical resection for pediatric atypical teratoid rhabdoid tumors

Abstract: Purpose To evaluate overall survival for atypical teratoid rhabdoid tumors (ATRTs) in relation to extent of surgical resection. Methods The neurosurgical tumor databases from three UK Pediatric centers (University Hospital of Wales, Alder Hey and Royal Manchester Children's Hospital) were analyzed. Patients with a diagnosis of ATRT were identified between 2000 and 2018. Data was collected regarding demographics, extent of resection, complications, and overall survival. Results Twenty-four patients diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“… 15 Similarly, the Foundation's figures illustrate that atypical teratoid rhabdoid tumor patients have been enrolled with an age range of 1 to 4 years and a mean average of 2 years which is again in line with the published literature which reflects a peak diagnosis at less than 3 years of age. 16 Retinoblastomas, have an age range of 6 months to 4 years at enrollment with a mean average of 1 year, 11 months which is consistent with the data provided in the American Cancer Society, Cancer Facts & Figures 2020 suggesting that the average age of children at diagnosis is 2 years. 17 If nothing else this supports the idea that for these tumors at least, the period between diagnosis and enrolment with the Foundation is very short.…”
Section: Data and Observations From Enrollment Recordssupporting
confidence: 83%
“… 15 Similarly, the Foundation's figures illustrate that atypical teratoid rhabdoid tumor patients have been enrolled with an age range of 1 to 4 years and a mean average of 2 years which is again in line with the published literature which reflects a peak diagnosis at less than 3 years of age. 16 Retinoblastomas, have an age range of 6 months to 4 years at enrollment with a mean average of 1 year, 11 months which is consistent with the data provided in the American Cancer Society, Cancer Facts & Figures 2020 suggesting that the average age of children at diagnosis is 2 years. 17 If nothing else this supports the idea that for these tumors at least, the period between diagnosis and enrolment with the Foundation is very short.…”
Section: Data and Observations From Enrollment Recordssupporting
confidence: 83%
“…13 Improved outcomes have also been associated with multimodal therapy, radiotherapy in patients older than 3 years of age, and gross total resection compared with less extensive surgery. 14,15 Our patient had no metastasis and underwent gross total resection. He was subsequently enrolled in the Saint Jude's Phase 2 Study of Alisertib Therapy for Rhabdoid Tumors (SJATRT) 16 and received craniospinal radiation along with Alisertib treatment.…”
Section: Atypical Teratoid Rhabdoid Tumormentioning
confidence: 84%
“…It has been shown that the extent of resection is critical to ATRT patient outcomes. Richards et al revealed that complete total resection had a significantly higher overall survival (66.6%) compared to near-total resection (29%) or subtotal resection (12.5%) in children with newly diagnosed ATRT [5].…”
Section: Discussionmentioning
confidence: 99%
“…A study revealed that complete total resection had a significantly higher overall survival (66.6%) compared with near-total resection (29%) or subtotal resection (12.5%) in children with newly diagnosed ATRT. 5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation